Edukasi Gizi Untuk Meningkatkan Pengetahuan Pola Makan Pada Pasien Diabetes Melitus Tipe 2 di Samarinda - Pasinggi, Miako; Wisnuwardani, Ratih Wirapuspita; K, Iriyani (JPM: Jurnal Pengabdian Masyarakat, 2025)
The prevalence of Diabetes Mellitus (DM) in Samarinda is the highest in East Kalimantan, driven by technological developments, environmental changes, and lifestyle factors. This community service aimed to provide nutrition education to improve dietary knowledge among people with DM, supporting better DM control and preventing complications. The education focused on the DM diet using the 3 J rule (Amount, Type, and Schedule of meals) and the Balanced Nutrition Meal Plate Guidelines, incorporating the “T Plate” eating model. A pretest-posttest design was employed, with knowledge assessed through a questionnaire of 10 true/false questions before and after the intervention. This service, contucted in partnership with the Palaran Health Center, included 22 participants, with 21 showing improved scores-an average from 73.18 to 88.64. This activity demontrates the effectiveness of nutrition education in enhancing dietary knowledge among DM patients.